Using Theory of Change to design and evaluate complex mental health interventions in low and middle income countries: the case of PRIME - Breuer Erica (Department of Public Health and Family Medicine, 2019)
Background: Many health interventions are complex and consist of several interacting components (Medical Research Council 2008). These components include multiple causal strands, outcomes and levels of governance and may result in unexpected outcomes and non-linear change (Glouberman and Zimmerman 2002). As such they present challenges to the design and evaluation of complex health interventions. Although broad theoretical guidance has been developed by the UK Medical Research Council (MRC) (Craig, Dieppe et al. 2008), it contains little practical guidance and has been criticised for not including theory driven approaches to evaluation such as Theory of Change (ToC) (Anderson 2008). De Silva, Breuer et al. (2014) have proposed that ToC may complement the MRC guidance on complex health interventions. Methods: This study explores how ToC can strengthen the design and evaluation of complex health interventions using the example of The Programme for Improving Mental Health Care (PRIME). PRIME is a research programme which aimed to develop, implement and evaluate the integration of mental health into primary health in districts or sub-districts in Ethiopia, India, Nepal, South Africa and Uganda. A ToC approach was used in addition to other approaches to design and evaluate these complex mental health interventions. Firstly, I conducted a systematic review to determine the extent to which ToC has been used to design and evaluate public health interventions. Secondly, I compared the process of developing the ToC between all five PRIME countries and reflected on the value of ToC workshops using a framework analysis of workshop documentation and interviews with facilitators. Thirdly, I explored the development of the ToCs within the programme as a whole and the implications for the development of the intervention and the choice of evaluation methods. Fourthly, I presented a ToC for the integration of mental health care in low and middle income countries. Fifthly, I demonstrated how ToC can be used as a framework for a qualitative comparative analysis of process and outcome data using longitudinal data from 10 PRIME implementation facilities in Nepal. Lastly, I provide a set of 10 key lessons learned from PRIME in the application of ToC to complex mental health interventions. Results I found that the ToC approach has been used for the design and evaluation of public health interventions since the 1990s. However, there is a lack of clear description of the use of ToC in the literature on public health interventions and inconsistency in how it is used. In applying the ToC approach to PRIME, I found that facilitators reported that ToC workshops were a valuable way to develop ToCs and that different stakeholders at the workshop contribute different types of information to the ToC process. Hierarchies within the health system are an important consideration for ToC workshops as power dynamics are likely to influence the functioning of the group. In addition, I found that the development of a cross country ToC can result in a programme theory which is relevant for complex multilevel intervention in different contexts. This ToC can provide a framework to map contextually relevant interventions and can be used to complement other intervention development approaches. The ToC can also be used to ensure indicators for all the short-, medium- and long-term outcomes are identified. However, combining process and outcome data analysis using the ToC is not straightforward. Qualitative Comparative Analysis (QCA) can be used to analyse process and outcome data in a single analysis in health services research. Conclusion: ToC can be used to strengthen the design and evaluation of complex health interventions and can be used to complement the MRC guidance in the design and evaluation of complex health interventions.